Implementing cost-optimal methodology in existing public buildings - Aelenei, Laura Elena (2016)
This study presents some preliminary results of an on-going European Project, RePublic_ZEB, where an analysis is conducted for identifying the cost optimal levels for the existing buildings, towards nearly Zero Energy Buildings (nZEB) performance. The analysis is applied to the reference building for an existing office building in five different countries: Italy, Portugal, Romania, Spain and Greece. The evaluation tool uses a new cost optimization procedure based on a sequential search- optimization technique considering discrete options is applied and the results will be presented in terms of optimal “package of measures”, energy consumption and global costs. Finally a cross-country analysis will be performed.